Engagement Enhancement Based on Human-in-the-Loop Optimization for Neural Rehabilitation - Wang, Jiaxing; Wang, Weiqun; Ren, Shixin; Shi, Weiguo; Hou, Zeng-Guang (Frontiers in Neurorobotics, 2020)
Enhancing patients' engagement is of great benefits for neural rehabilitation. However, physiological and neurological differences among individuals can cause divergent responses to the same task, and the responses can further change considerably during the training, both of which make the engagement enhancement challenging. This challenge can be overcome by training task optimization based on subjects' responses. To this goal, an engagement enhancement method based on human-in-the-loop optimization is proposed in this paper. Firstly, an interactive speed-tracking riding game is designed as the training task, in which four reference speed curves (RSCs) are designed to construct the reference trajectory in each generation. Each RSC is modeled using a piecewise function, which is determined by the starting velocity, transient time and end velocity. Based on the parameterized model, the difficulty of the training task, which is a key factor affecting the engagement, can be optimized. Then, the objective function is designed by consideration of the tracking accuracy and the surface electromyogram (sEMG) based muscle activation, thus subjects' physical and physiological responses can be evaluated simultaneously. Moreover, a covariance matrix adaption evolution strategy, which is relatively tolerant of both measurement noises and human adaptation, is used to generate the optimal parameters of the RSCs periodically. By optimization of the RSCs persistently, the objective function can be maximized and subjects' engagement can be enhanced. Finally, the performance of the proposed method is demonstrated by the validation and comparison experiments. The results show that both subjects' sEMG based motor engagement and electroencephalography based neural engagement can be improved significantly and maintained at a high level.